2018
DOI: 10.3934/cpaa.2018115
|View full text |Cite
|
Sign up to set email alerts
|

On the product in Besov-Lorentz-Morrey spaces and existence of solutions for the stationary Boussinesq equations

Abstract: This paper is devoted to the Boussinesq equations that models natural convection in a viscous fluid by coupling Navier-Stokes and heat equations via a zero order approximation. We consider the problem in R n and prove the existence of stationary solutions in critical Besov-Lorentz-Morrey spaces. For that, we prove some estimates for the product of distributions in these spaces, as well as Bernstein inequalities and Mihlin multiplier type results in our setting. Considering in particular the decoupled case, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For instance, Leray [15] and Ladyzhenskaya [14] showed the existence of strong solutions to (SNS), and Heywood [10] constructed solutions of (SNS) as a limit of solutions of the nonstationary Navier-Stokes equations. Later on, Chen [4] showed that for every small external force having a divergence-form 𝑓 = ∇ ⋅ 𝐹, 𝐹 ∈ 𝐿 TSURUMI [13] and weak 𝐿 𝑛 (ℝ 𝑛 ) space [12], which is later generalized by Ferreira, Pérez-López, and Villamizar-Roa [5] who studied solutions to the stationary Boussinesq equations in critical Besov-Lorentz-Morrey spaces. Recently, the existence and uniqueness of solutions to (SNS) in the homogeneous Besov spaces on ℝ 𝑛 were well studied by Kaneko-Kozono-Shimizu [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Leray [15] and Ladyzhenskaya [14] showed the existence of strong solutions to (SNS), and Heywood [10] constructed solutions of (SNS) as a limit of solutions of the nonstationary Navier-Stokes equations. Later on, Chen [4] showed that for every small external force having a divergence-form 𝑓 = ∇ ⋅ 𝐹, 𝐹 ∈ 𝐿 TSURUMI [13] and weak 𝐿 𝑛 (ℝ 𝑛 ) space [12], which is later generalized by Ferreira, Pérez-López, and Villamizar-Roa [5] who studied solutions to the stationary Boussinesq equations in critical Besov-Lorentz-Morrey spaces. Recently, the existence and uniqueness of solutions to (SNS) in the homogeneous Besov spaces on ℝ 𝑛 were well studied by Kaneko-Kozono-Shimizu [11].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Chen [4] showed that for every small external force having a divergence‐form f=·F$f=\nabla \cdot F$, FLn2(double-struckRn)$F\in L^{\frac{n}{2}}(\mathbb {R}^n)$, there exists a unique strong solution u of (SNS) in Ln(double-struckRn)$L^n (\mathbb {R}^n)$. After that, Kozono–Yamazaki showed the existence of solutions in critical Morrey spaces [13] and weak Ln(double-struckRn)$L^n(\mathbb {R}^n)$ space [12], which is later generalized by Ferreira, Pérez‐López, and Villamizar‐Roa [5] who studied solutions to the stationary Boussinesq equations in critical Besov–Lorentz–Morrey spaces. Recently, the existence and uniqueness of solutions to (SNS) in the homogeneous Besov spaces on double-struckRn$\mathbb {R}^n$ were well studied by Kaneko–Kozono–Shimizu [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, they established a decay estimative for this global solution. In the work ( [19], 2018) L.C.F. Ferreira, J.E.…”
Section: Introductionmentioning
confidence: 99%
“…without invoke Kato's approach, see [13] for weak-Morrey spaces, see [14] for Besovweak-Morrey spaces and see [36] for weak-L p spaces. For stationary Boussinesq equations, see [15] for Besov-weak-Morrey spaces and see [16] for weak-L p spaces. Choosing a specific h λ p -atom and using discrete Calderón reproducing formula in Hardy-Morrey spaces, from atomic decomposition theorem the authors [23] characterized the continuity of I α : h λ p (dν) → h λ * q (dµ) by using the growth condition µ β < ∞, provided that 0 < p < q < 1 satisfies (1.4).…”
Section: Introductionmentioning
confidence: 99%